Canadian Veteran chronic disease prevalence and health services use in the five years following release: a matched retrospective cohort study using routinely collected data - Alyson L. Mahar; Kate St. Cyr; Jennifer E. Enns; Alice B. Aiken; Marlo Whitehead; Heidi Cramm; Paul Kurdyak (BMC, 2022)
Abstract Background Occupational exposures may result in Canadian military Veterans having poorer health and higher use of health services after transitioning to civilian life compared to the general population. However, few studies have documented the physical health and health services use of Veterans in Canada, and thus there is limited evidence to inform public health policy and resource allocation. Methods In a retrospective, matched cohort of Veterans and the Ontario general population between 1990-2019, we used routinely collected provincial administrative health data to examine chronic disease prevalence and health service use. Veterans were defined as former members of the Canadian Armed Forces or RCMP. Crude and adjusted effect estimates, and 95% confidence limits were calculated using logistic regression (asthma, COPD, diabetes, myocardial infarction, rheumatoid arthritis, family physician, specialist, emergency department, and home care visits, as well as hospitalizations). Modified Poisson was used to estimate relative differences in the prevalence of hypertension. Poisson regression compares rates of health services use between the two groups. Results The study included 30,576 Veterans and 122,293 matched civilians. In the first five years after transition to civilian life, Veterans were less likely than the general population to experience asthma (RR 0.50, 95% CI 0.48-0.53), COPD (RR 0.32, 95% CI 0.29-0.36), hypertension (RR 0.74, 95% CI 0.71-0.76), diabetes (RR 0.71, 95% CI 0.67-0.76), myocardial infarction (RR 0.76, 95% CI 0.63-0.92), and rheumatoid arthritis (RR 0.74, 95% CI 0.60-0.92). Compared to the general population, Veterans had greater odds of visiting a primary care physician (OR 1.76, 95% CI 1.70-1.83) or specialist physician (OR 1.39, 95% CI 1.35-1.42) at least once in the five-year period and lower odds of visiting the emergency department (OR 0.95, 95% CI 0.92-0.97). Risks of hospitalization and of receiving home care services were similar in both groups. Conclusions Despite a lower burden of comorbidities, Veterans had slightly higher physician visit rates. While these visits may reflect an underlying need for services, our findings suggest that Canadian Veterans have good access to primary and specialty health care. But in light of contradictory findings in other jurisdictions, the underlying reasons for our findings warrant further study.